Cork and metals: a review - C. C. da Ponte-e-Sousa, João Carlos a.; Neto-Vaz, António Manuel; de C. C. da Ponte-e-Sousa, João Carlos a.; Neto-Vaz, António Manuel (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.
Keywords: ash content; cork (voyant); metals; mineral elements

Cork and metals: a review - C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel; de C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.
Keywords: ash content; cork (voyant); metals; mineral elements

Characteristics of internal porosity of cork container media - Ordovas, J; Carmona, E; Moreno, M T; Ortega, M C (HORTSCIENCE, 1996)
The structure of cork (Quercus suber L.) bark presents a series of characteristics, suggesting that internal porosity is partly occluded. This study determined the porosity in the waste cork industry (C) and when such waste product had been composted during 4 (CC-4), 7 (CC-7), and 10.5 months (CC-10.5). The particle density of the intact and finely ground material differed significantly in all particle size ranges larger than 0.5 mm. The porosity of the cork substrates ranged from 80% to 94% of the total volume, according to granulometry and the degree of decomposition. However, large particles and less decomposed material with a high porosity had up to 10% of the total volume as occluded pores. The material's effective porosity varied slightly between the various particle sizes and degrees of decomposition, which ranged between 80% and 89%, having an average value of 85%. The ash content was highly correlated with the particle density of the finely ground material. Nevertheless, and due to occluded porosity, we cannot estimate the `'effective porosity'' from the ashes; therefore, we must resort to techniques that involve the displacement of a fluid, such as liquids or gas pycnometry or submersion.
Keywords: ash content; effective porosity; particle density; total porosity

Characteristics of internal porosity of cork container media - Ordovas, J.; Carmona, E.; Moreno, M. T.; Ortega, M. C. (HORTSCIENCE, 1996)
The structure of cork (Quercus suber L.) bark presents a series of characteristics, suggesting that internal porosity is partly occluded. This study determined the porosity in the waste cork industry (C) and when such waste product had been composted during 4 (CC-4), 7 (CC-7), and 10.5 months (CC-10.5). The particle density of the intact and finely ground material differed significantly in all particle size ranges larger than 0.5 mm. The porosity of the cork substrates ranged from 80% to 94% of the total volume, according to granulometry and the degree of decomposition. However, large particles and less decomposed material with a high porosity had up to 10% of the total volume as occluded pores. The material's effective porosity varied slightly between the various particle sizes and degrees of decomposition, which ranged between 80% and 89%, having an average value of 85%. The ash content was highly correlated with the particle density of the finely ground material. Nevertheless, and due to occluded porosity, we cannot estimate the `'effective porosity'' from the ashes; therefore, we must resort to techniques that involve the displacement of a fluid, such as liquids or gas pycnometry or submersion.
The following values have no corresponding Zotero field: pub-location: 701 NORTH SAINT ASAPH STREET, ALEXANDRIA, VA 22314-1998 publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: ash content; effective porosity; particle density; total porosity